IMPROVING ENGLISH STUDENTS’ READING COMPREHENSION AND LEARNING DIFFICULTY BASED ON SOME VARIABLES - Mohamad Ahmad Saleem Khasawneh (JURNAL PAJAR (Pendidikan dan Pengajaran), 2022)
Experimental study in this article is aimed to investigate the effect of reading comprehension improvement for English language students toward their learning difficulty by using the reading speed strategy and identify the effect of gender and teaching method on the improvement of students’ reading comprehension. To achieve the objectives, a test was prepared to measure students’ reading comprehension after ensuring validity and reliability. The study involved 200 English students of the schools registered in Direktorat Pendidikan Wilayah Irbid II in the academic year of 2020/2021. They were 80 males and females, who are selected by using a simple method. The sample was categorized into two experimental groups with training and two control groups with the same material learning in a traditional method. The test was distributed to the groups before applying the strategy to ensure the whole group. The result showed that there are differences between the mean score of experimental group and the mean score of control group, and in favor of the experimental group. The result also showed that there are no differences among the mean score of students, which is attributed to gender.